Preservation of titanosaur egg clutches in Upper Cretaceous cumulative palaeosols (Los Llanos Formation, La Rioja, Argentina) - Basilici, Giorgio (2017)
Studies of the palaeobiology of titanosaur eggs are significantly more common than studies of titanosaur-egg-bearing strata. Nevertheless, the latter provide significant insight into palaeoenvironmental conditions associated with the egg-laying behaviour. This study examines titanosaur-egg-bearing strata of the Upper Cretaceous Los Llanos Formation (La Rioja, Argentina) and relates them to the laying and preservation of titanosaur egg clutches. Los Llanos Formation is a predominantly sandstone succession throughout represented by palaeosol profiles. Five titanosaur egg clutches were recovered from the Bw horizon of an Inceptisol profile. This palaeosol type, named Tama pedotype, constitutes 69% of the entire succession, by thickness. Rare planar, and undulating lamination and cross stratification, quartz-grain surface microtextures and ventifacts are indicative of the interaction of fluvial-aeolian processes of sedimentation during accumulation of the parent material on the distal part of a coalescent alluvial fan system (bajada). Highly abundant root traces, reddish colour, clay coatings and calcium carbonate nodules testify that the Tama pedotype had abundant vegetation cover, and was developed in well-drained conditions under the influence of a semiarid climate regime. Palaeosol horizons with exaggerated thickness and diffuse boundaries indicate a cumulative pedotype, whereby the soil developed in response to continuous accretion via on-going sedimentary processes.Morphological features of eggshells suggest that titanosaurs dug holes in the topographic surface to lay eggs. Thus, palaeosols seem to have been putative areas for the laying of titanosaur eggs. Actually, it is uncommon for palaeosols to constitute sites for the preservation of eggs, since soils typically develop in response to long episodes of weathering. However, cumulative palaeosols can provide ideal conditions for egg burial and preservation. In cumulative soils, the residence time of an object within the weatherable thickness of a soil is reduced to < 103 years, thereby significantly increasing the long-term preservation potential of eggs.